2008
DOI: 10.1039/b705969h
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring plasmonic substrates for surface enhanced spectroscopies

Abstract: Our understanding of how the geometry of metallic nanostructures controls the properties of their surface plasmons, based on plasmon hybridization, is useful for developing high-performance substrates for surface enhanced spectroscopies. In this tutorial review, we outline the design of metallic nanostructures tailored specifically for providing electromagnetic enhancements for surface enhanced Raman scattering (SERS). The concepts developed for nanoshell-based substrates can be generalized to other nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
465
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(469 citation statements)
references
References 56 publications
3
465
0
1
Order By: Relevance
“…A consequence of the interaction is the ability to concentrate light fields with orders of magnitude enhancement at visible and near infrared (NIR) wavelengths to the subwavelength scale. Such enhancements find profound applications in improving the efficiencies of several phenomena such as fluorescence,1, 2, 3 surface‐enhanced Raman spectroscopy (SERS),4, 5, 6, 7, 8 surface‐enhanced infrared absorption,9, 10, 11 single‐molecule detection,12, 13 nonlinear optical effects,14, 15, 16 and multiphoton polymerization 17, 18. Exploiting this highly confined optical field is crucial, but simultaneously it is also challenging to position the desired molecules or particles accurately at these locations.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the interaction is the ability to concentrate light fields with orders of magnitude enhancement at visible and near infrared (NIR) wavelengths to the subwavelength scale. Such enhancements find profound applications in improving the efficiencies of several phenomena such as fluorescence,1, 2, 3 surface‐enhanced Raman spectroscopy (SERS),4, 5, 6, 7, 8 surface‐enhanced infrared absorption,9, 10, 11 single‐molecule detection,12, 13 nonlinear optical effects,14, 15, 16 and multiphoton polymerization 17, 18. Exploiting this highly confined optical field is crucial, but simultaneously it is also challenging to position the desired molecules or particles accurately at these locations.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is a powerful spectroscopy technique that can provide non-destructive and ultra-sensitive characterization down to single molecular levels which are attached to nanometer sized metallic structures [18,19]. SERS was first discovered by Fleischmann et al [20] in 1974 who observed intense Raman scattering on the molecular pyridine adsorbed onto a roughened silver electrode surface from aqueous solution.…”
Section: Surface-enhanced Spectroscopymentioning
confidence: 99%
“…In SEIRA, vibrational modes of molecules with a change of dipole moment perpendicular to the substrate are enhanced and therefore this technique has potential for providing the information about orientation of adsorbed species with respect to the surface. Since its invention, SEIRA has been used in numerous applications in chemical analysis and characterization and biochemical sensing [75].…”
Section: Surface Enhanced Infrared Absorptionmentioning
confidence: 99%